Benzylic Functionalization of Anthrones via the Asymmetric Ring Opening of Oxabicycles Utilizing a Fourth‐Generation Rhodium Catalytic System. Issue 40 (27th August 2015) - Loh, Charles C. J.; Fang, Xiang; Peters, Brendan; Lautens, Mark
Abstract: While anthrones exist as privileged scaffolds in bioactive molecules, the enantioselective functionalization of anthrones is surprisingly scarce in the literature, with no asymmetric transition metal catalyzed example to date. Herein, we report the first asymmetric transition metal catalyzed benzylic functionalization of anthrones through the rhodium(I) catalyzed desymmetrization of oxabicycles. As previously developed rhodium(I) systems were found to be unsuitable for this substrate, a new robust fourth‐generation [Rh(cod)OH]2 based catalytic system was developed to address synthetic challenges in this protocol. Abstract : It's now version 4! A robust fourth‐generation [Rh(cod)OH]2 based catalytic system was developed for the asymmetric ring opening reaction of oxabicycles by the benzylic functionalization of anthrones. This protocol showcases the very first asymmetric transition metal‐catalyzed functionalization of anthrones and opens up for anthrones a new SN 2′ reaction class, since such substrates were not previously known to react beyond the conjugated Michael‐type systems.